Sistem Informasi Pusat Pengembangan Karir Mahasiswa Berbasis Web pada Politeknik Negeri Ketapang - Eka Wahyudi; Novi Indah Pradasari; Darmanto Darmanto (STEKOM PRESS, 2021)
This research aims to build a career development center information system at the Ketapang State Polytechnic. The results of this research are then used as a scientific study in the field of design and development of information systems. In addition, this career development center information system can be implemented at the Ketapang State Polytechnic so that it can contribute to the accreditation process of institutions and study programs, as a forum for building alumni networks and the availability of an alumni database, as a collection of important input/information for the development and improvement of universities. higher education (administration, curriculum and study design). Career centers at universities function to bridge the information needs of the world of work required by universities and to answer the challenges of the world of work. This career development center information system is based on the needs of alumni, tracer studies for campus accreditation, knowing the educational outcomes produced by universities, knowing the contribution of universities to existing competencies in the world of work, for monitoring college graduates when entering the word